Crowdsourcing 101: A Few Basics to Make You the Leader of the Pack. Issue 2 (March 2013) - Parvanta, Claudia; Roth, Yannig; Keller, Heidi
Crowdsourcing is a problem-solving approach that taps the knowledge, energy, and creativity of a global, online community. Like marketing, crowdsourcing originated and continues to evolve in the private sector. Health communicators and social marketers can use crowdsourcing across the research-development-dissemination process. This article provides an overview of crowdsourcing and how it can be used to speed up and enhance social marketing and health communication. Nielsen's 1/9/90% model is presented as a guide for engaging appropriate crowds for tasks throughout the development process. The four Fs that motivate online contributors—Fun, Feeling good (fulfillment), Fame, and Fortune—are also presented as ways of incentivizing crowd engagement and matching the incentive to the task at hand. Crowdsourcing resources, such as curating agencies, websites, and crowd labor markets, can be tremendous force multipliers. If done strategically, crowdsourcing has the promise of giving well-researched and creative social marketing results for less money and in less time than traditional methods.